Development and prototyping of an innovative design for automatic paper bag making machine - Nithul, P.; Vikas, V. K. (Recent Research in Science and Technology, 2023)
The Plastic Waste Management Amendment Rules, 2021, already prohibit the manufacture, import, stocking, distribution, sale, and use of plastic carry bags having a thickness of less than 75 microns. They also provide for a ban on plastic carry bags with a thickness of less than 120 microns as of December 31, 2022. So, there is an increasing demand for paper bags. The already existing paper bag-making machines are expensive and consume 25-50 square meters for their operation. A machine whose initial cost is less, which does not require large space consumption and operates with simple technologies, can be used for small-scale production. This will help the manufacturer earn money through the small-scale production of paper bags. The demand for paper bags is continuously increasing, so this project aims to develop an economical and easily fabricable machine with simple methods that promote the use of paper bags instead of plastic carry bags and helps reduce the impact on the environment.